Chronic Pain in Children: A Look at the Referral Process to a Pediatric Pain Clinic - Giovanni Cucchiaro; Jennifer Schwartz; Alec Hutchason; Beatriz Ornelas (International Journal of Pediatrics)
We reviewed the referral pattern of children with chronic pain to a specialized pediatric pain clinic. Data were obtained from referring physicians and medical records and during an interview with patients and their parents by physicians and a psychologist. We analyzed the following: referral diagnosis, demographics, duration of symptoms, number of physicians previously consulted, school attendance, sports activities, presence of psychological disorders, final team diagnosis, and outcomes. Children had been experiencing pain for 34±55 months. Patients had consulted on average 3 physicians in addition to their pediatrician. 32% of the patients had missed at least 10 days of school in a calendar year, and 47% had stopped playing sports. 15% had an operation because of pain that had been unsuccessful. The most common missed diagnosis was anxiety (25%) and depression (13%). 69% of the patients were back to school and/or playing sports within 4 months from our initial consultation. 32% of the patients did not make any progress during the follow-up period. The most common reasons for failure to improve were no compliance with the recommended treatments and poorly controlled major mood disorder. The time to refer children with chronic pain for specialized care could be extremely long causing significant social and psychological consequence.